Faktor Penghambat Penggunaan Tracer Pada Unit Penyimpanan Berkas Rekam Medis Pasien Rawat Jalan di Rumah Sakit - Putri, Sartika Maulida; Sarah, Siti; Anita, Julia; Khatimah, Cut Husnul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Medical record tracers are a replacement for medical records that will be removed from storage for any purpose, usually made of strong and colored material. Factors that cause delays in the use of tracers in storage rooms include the lack of staff with educational backgrounds in medical records, the absence of special officers in the storage department and the non-implementation of SOPs regarding the use of tracers. The aim of this research is to determine the factors inhibiting the use of tracers in the outpatient medical record storage unit at Bhayangkara Hospital Banda Aceh in 2023. This research was conducted in the outpatient storage room at Bhayangkara Hospital Banda Aceh, 15-20 May 2023. This type of research is Descriptive Qualitative. The population of this study consisted of 9 medical records officers. The research sample consisted of 3 people specifically for outpatient medical records officers using Purposive Sampling Technique. The results of the research show that in the use of tracers in the outpatient medical record file storage unit, the human resource factor is in the